Factors Associated with Attempted External Cephalic Version for Fetal Malpresentation at Term - Limaye, Meghana; Abdullahi, Najma; Has, Phinnara; Danilack, Valery A.; Froehlich, Rosemary; Werner, Erika (American Journal of Perinatology Reports, 2019)
Objective To assess differences in patient characteristics between women who did and did not undergo attempted external cephalic version (ECV) for fetal malpresentation at term.Study Design This was a retrospective cohort study of women with a singleton gestation and noncephalic presentation at > 37.0 weeks between October 2014 and October 2015. We compared demographic and clinical characteristics of women who did and did not undergo attempted ECV and assessed the reasons that women did not attempt ECV.Results Among 215 women, only 51 (24%) attempted ECV. There were no differences in age, race, insurance type, or body mass index between women who underwent attempted ECV and those who did not. Women who underwent ECV were significantly more likely to have had a prior vaginal delivery (69 vs. 36%, p < 0.001). Seventy-six women (46%) declined ECV. Women who declined ECV were more likely to be nulliparous than those who accepted the procedure (66 vs. 29%, p < 0.001). Among women who had ECV, the success rate was 55%. There were no adverse events after attempted ECV in this cohort.Conclusion Among women with fetal malpresentation at term, those without a prior vaginal delivery were significantly less likely to undergo attempted ECV.
Keywords: external cephalic version; fetal malpresentation; prevention of primary cesarean delivery; utilization of external cephalic version